Global arginine bioavailability, a marker of nitric oxide synthetic capacity, is decreased in PTSD and correlated with symptom severity and markers of inflammation - Bersani, Francesco Saverio; Wolkowitz, Owen M.; Lindqvist, Daniel; Yehuda, Rachel; Flory, Janine; Bierer, Linda M.; Makotine, Iouri; Abu-Amara, Duna; Coy, Michelle; Reus, Victor I.; Epel, Elissa S.; Marmar, Charles; et al. (Brain, behavior, and immunity, 2016)
•The “global arginine bioavailability ratio” (GABR) is a marker of nitric oxide production.•The GABR is decreased in male war veterans with PTSD.•The GABR is inversely associated with markers of inflammation.•The GABR is inversely associated with psychopathological severity. Psychiatric, physical and biological aspects of posttraumatic stress disorder (PTSD) may be associated with dysfunctions in several cellular processes including nitric oxide (NO) production. NO is synthesized from arginine in a reaction carried out by NO synthase (NOS) enzymes. The recently introduced “global arginine bioavailability ratio” (GABR; ratio of arginine to [ornithine+citrulline]) has been proposed as a reliable approximation of NO synthetic capacity in vivo. The objectives of the present study were to test the hypotheses that (i) subjects with combat-related PTSD have lower GABR scores than combat controls, (ii) GABR score is inversely associated with the severity of psychopathological measures, (iii) GABR score is inversely associated with markers of inflammation. Metabolic profiling for plasma samples (i.e. arginine, citrulline and ornithine) and inflammation markers (interleukin [IL]-6, IL-1β, tumor necrosis factor [TNF]-α, interferon [IFN]-γ and C-reactive protein [CRP]) were assessed in 56 combat-exposed males with PTSD and 65 combat-exposed males without PTSD. We assessed severity of PTSD (Clinician Administered PTSD Scale [CAPS]) and depression (Beck Depression Inventory-II [BDI-II]) as well as history of early life trauma (Early Trauma Inventory [ETI]) and affectivity (Positive and Negative Affect Schedule [PANAS]). The GABR value was (i) significantly lower in PTSD subjects compared to controls (p=0.001), (ii) significantly inversely correlated with markers of inflammation including IL6 (p=0.04) and TNFα (p=0.02), and (iii) significantly inversely correlated with CAPS current (p=0.001) and lifetime (p<0.001) subscales, ETI (p=0.045) and PANAS negative (p=0.006). Adding antidepressant use or MDD diagnosis as covariates led to similar results. Adding age and BMI as covariates also led to similar results, with the exception of IL6 and ETI losing their significant association with GABR. This study provides the first evidence that global arginine bioavailability, a marker of NO synthetic capacity in vivo, is lower in veterans with PTSD and is negatively associated with some markers of inflammation as well as with measures of PTSD symptom severity, negative affectivity and childhood adverse experiences. These findings add to the accumulating evidence that specific cellular dysfunction may be associated with the symptomatology of PTSD and may help to explain the higher burden of cardio-metabolic disturbances seen in this disorder.